Hematologic and Clinical Features of Thalassemia Patients with Early or Late Onset Transfusion in East Java, Indonesia - Retno Dwi Wulandari (Journal of Global Pharma Technology, 2016)
Thalassemia is a genetic disorder of hemoglobin production which causes chronic anemia. Complete blood count showed lower HbA, MCV, MCH, increase RDW-CV and increase HbA2 (>3,5%) and HbF (>1,5%). Thalassemia major patients need regular and lifelong blood transfusion which started early in life. Thalassemia intermedia, usually with milder symptoms, require blood transfusion at later age, with lower transfusion rate. This study aims to compare hematologic, HbA2 and HbF profiles as well as height, weight, Body Mass Index and spleen size in thalassemia patients grouped based on transfusion start whether in early or later age (before or after 10 yo). Results showed that the hematologic, HbA2 and HbF profiles were not significantly different in both groups. The clinical profiles i.e. Height and weight were below 3rd percentile in both groups; low BMI and more patients underwent splenectomy in group of those with early onset blood transfusion.Keywords: Thalassemia, Transfusion, Hematologic, Height, Weight, BMI.